Genetic analysis of epidermal growth factor action: assignment of human epidermal growth factor receptor gene to chromosome 7. - Davies, R L (1980)
Purified murine epidermal growth factor (EGF) binds to mouse and human cells. Two mouse transformed cell lines of different origins, PG19 and B82, were found to lack EGF receptors (EGFR). The defect in each of these two cell lines seems to be identical because they fail to complement each other. Somatic cell hybrids between these EGFR-deficient mouse cells and human cells expressing EGFR were produced. Several of these hybrids bound labeled EGF. Detailed cytogenetic analysis of these cell hybrids, followed by correlation of EGFR expression with human chromosomes revealed that EGFR presence correlated with human chromosome 7. The results suggest that the structural gene or a gene necessary for expression of the human EGF receptor is located on human chromosome 7.